BREAKING THE GLASS CEILING: EMPOWERING FEMALE LEADERSHIP IN CENTRAL ASIA'S MINING SECTOR: Received: 28th November 2024, Revised: 10th February 2025, 3rd March 2025, Accepted: 30th May 2025, Date of Publication: 12th November 2025 - Ainur Orazbayeva, (PEOPLE: International Journal of Social Sciences, 2025)
In the context of corporate law in Central Asia's mineral resources mining sector, there is an increasing debate on the inclusion of female leaders. This article will investigate this topic, focusing on how women are navigating leadership roles in a traditionally male-dominated business. The study offers light on the opportunities and challenges that female leaders confront in mining. It focuses on the challenges they face, including gender biases and a lack of supportive laws, while also highlighting their contributions to innovation and good business practices. By making strategic recommendations, the article hopes to foster a more inclusive atmosphere for female leadership in the Central Asian mining industry. Hence, the mining sector can unlock a wealth of talent and expertise, and foster sustainable development by empowering female leadership in the region.